Formulation Of Regional Management Singbebas - Rochmawati, Ida; Arifin, Arifin (Journal Research of Social Science, Economics, and Management, 2023)
The formulation of regional management strategies plays a pivotal role in the sustainable development and growth of a region. This abstract introduces the concept of "Singbebas Regional Management" as a framework for the effective governance and development of a specific region. It outlines the key components and strategies involved in the formulation of Singbebas Regional Management, focusing on regional autonomy, economic development, and social well-being. This abstract provides a brief overview of the comprehensive study that delves into the principles and practices of Singbebas Regional Management and its potential implications for regional development.